PROSEDUR PENGUJIAN SUBSTANTIF SALDO KAS DAN SETARA KAS PT XYZ OLEH KANTOR AKUNTAN PUBLIK ACHSIN HANDOKO TOMO - Salsadella Rifaniya, (2020)
Auditing the cash and equivalent accounts is the most important part required by the public accountants office to audit the company's financial statements. The writer in the practice of field work had an opportunity to audit the cash and cash equivalent accounts owned by PT XYZ, one of the companies that specialized in power plants. The purpose of auditing cash and the cash equivalent accounts is to ensure that the cash and cash equivalent balance presented by the company as of the balance sheet date have been disclosed appropriately with the appropriate amount. The audit cash and cash equivalent accounts is performed according to established auditing programs. In the drafting of this final assignment report, The writer compares the audit procedure of cash and cash equivalent learned in lectures with direct practice in the field in which after comparison the authors have concluded that the substantive testing procedure of cash and cash equivalent balance of PT XYZ in accordance with the knowledge learned during in the lectures and the results of the auditing results claim that substantive testing procedures for the balance of cash and cash equivalent of PT XYZ conducted by public accountant's office of Achsin Handoko Tomo was declared reasonable and free from material misstatement.